Stylistic Analysis of Figurative Language at the ARTJOG 2025 Art Description Discourse - Ikvina Hasanatika; Muktar Garba (Universitas Negeri Semarang, 2026)
Discourse in art exhibitions serves as a communication bridge, translating visual ideas that are often abstract and polysemous. This research aims to describe the forms and connotative meanings of figurative language used in the descriptive discourse of the ARTJOG 2025 exhibition,